The Impact of Fiscal Rules on Public Debt and Public Deficits Based on the Budget Institutions Approach - İlter Ünlükaplan; Ebru Yalçın (International Journal of Public Finance, 2024)
The budget institutions approach states that the differences between the public finance indicators of the countries are affected not only by economic conditions but also by institutional and political factors. Accordingly in order to prevent excessive public debt and public deficits, fiscal governance criteria must be established during the budget process.In this paper, the impact of fiscal rules applied in 21 EU countries on public debts and public deficits was tested using the 1995-2016 period data by Westerlund and Edgerton (2007) panel cointegration method. Considering the Fiscal Rule Index (Eurostat 2019) for the design of fiscal rules, we show that well-designed rules reduce public deficits but have no statistically significant effect on public debt.